SAT0124 Lymphopenia in Early Arthritis: Impact on Diagnosis and Prognosis during the First 3 Years (Espoir Cohort). (10th June 2014) - Duquenne, C.; Cornec, D.; Marhadour, T.; Jousse-Joulin, S.; Cantagrel, A.; Pavy, S.; Devauchelle-pensec, V.; Saraux, A.
Abstract : Background: In early arthritis, detection of lymphopenia may help clinician for diagnosis (connective tissue diseases, viral infections, hemopathies) or prognosis (systemic manifestations). An increased risk of infection should be anticipated when immunosuppressive treatment is prescribed. Objectives: The aim of this study was to determine the prevalence of lymphopenia during early arthritis, to assess the risk of its persistence, its diagnostic and prognostic value. Methods: The French Society for Rheumatology established a nationwide, longitudinal, prospective cohort, the ESPOIR cohort, to enable investigations of the diagnosis, outcome markers, epidemiology, pathogenesis, and medico-economics of early arthritis and RA. Patients were included if they were older than 18 years and younger than 70 years, had swelling of at least two joints for 6 weeks with a symptom duration no longer than 6 months, and had no prior treatment with DMARDs or glucocorticoids; however, the use of glucocorticoids for ≤2 weeks, in a mean dosage ≤20 mg/day and with discontinuation for at least the past 2 weeks, did not prevent study inclusion. Patients who were included were evaluated every 6 months for 2 years then once a year for at least 10 years. 813 patients with recent arthritis were included in the cohort ESPOIR. Patients had a clinical examination, laboratory tests (viral serology, immunological tests, cytokine profile), and radiographs. To determine the prevalence, associated factors, diagnosis and prognostic impact of persistent lymphopenia in early inflammatory joint disease, naive of lymphopenic treatment, we analyzed patients with lymphopenia at baseline and those with persistent lymphopenia at 3 years. Lymphopenia was defined by the rate of blood lymphocytes <1000/mm≥, threshold retained as significant in many studies. We studied the prevalence of lymphopenia at baseline and at three years. Results: At baseline, 50/813 (6.2%) patients had lymphopenia. They had more often positive rheumatoid factor (p=0.02), cytopenias (p≤0.05), a higher CRP and DAS28 (p≤0.05), and hepatitis C (p=0.05) than the remainders. There were no difference in the cytokine profile and radiological progression. Diagnostics after 3 years were 27 RA, 15 unclassified arthritis, 3 SLE, 2 spondyloarthritis, one Sjögren's syndrome, hematologic disease and fibromyalgia. Only 15/609 patients (2.5%) had persistent lymphopenia at 3 years. In 5 of these 15 patients, a cause of lymphopenia was found (SLE, hepatitis C, under nutrition, azathioprine and tamoxifen treatments). None had PVB19, HIV or HBV infection. None developed any infection, solid or hematologic neoplasia during the follow-up. Diagnostics were 6 RA, 6 unclassified arthritis, one SLE, spondyloarthritis and fibromyalgia. Conclusions: Lymphopenia in early arthritis was rare and require to search another disease than RA. However, the majority of patients have active RA and cytopenias. The majority of our lymphopenic patients do not present lymphopenia during the disease course, even when they received methotrexate. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3228